2020
DOI: 10.1080/17453674.2020.1840111
|View full text |Cite
|
Sign up to set email alerts
|

The impact of socioeconomic status on the utilization of total hip arthroplasty during 1995–2017: 104,055 THA cases and 520,275 population controls from national databases in Denmark

Abstract: Background and purpose — In Denmark, all citizens are guaranteed free access to medical care, which should minimize socioeconomic status (SES) inequalities. We examined the association between SES and the utilization of total hip arthroplasty (THA) by age and over time. Patients and methods — Data on education, income, liquid assets, and occupation on 104,055 THA cases and 520,275 population controls were obtained from Danish health registers. We used logistic regression to estimate adjusted odds ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…Socioeconomic inequality in health is increasingly recognized as an important public health issue (Agabiti et al 2007). Socioeconomic status (SES) is associated with access to total hip arthroplasty (THA) and with greater vulnerability to complications after THA, all in favor of high status (Agabiti et al 2007, Weiss et al 2019, Edwards et al 2021. However, few studies have investigated the impact of SES on the risk of revision and mortality and they all present contradicting results, from showing that low SES was associated with a higher risk of early mortality after a THA, to finding no association among SES, revision, and mortality (Mahomed et al 2003, Agabiti et al 2007, Jenkins et al 2009, Peltola and Järvelin 2014, Maradit Kremers et al 2015.…”
mentioning
confidence: 99%
“…Socioeconomic inequality in health is increasingly recognized as an important public health issue (Agabiti et al 2007). Socioeconomic status (SES) is associated with access to total hip arthroplasty (THA) and with greater vulnerability to complications after THA, all in favor of high status (Agabiti et al 2007, Weiss et al 2019, Edwards et al 2021. However, few studies have investigated the impact of SES on the risk of revision and mortality and they all present contradicting results, from showing that low SES was associated with a higher risk of early mortality after a THA, to finding no association among SES, revision, and mortality (Mahomed et al 2003, Agabiti et al 2007, Jenkins et al 2009, Peltola and Järvelin 2014, Maradit Kremers et al 2015.…”
mentioning
confidence: 99%
“…There has been evidence of poorer outcomes after arthroplasty among people with poorer socioeconomic circumstances. Edwards et al highlighted a social gradient in the demand for THA in Denmark 33. They found that the demand for THA was highest among those of lowest educational attainment and lowest household incomes among people aged 45–55 years, effects that diminished with increasing age 33.…”
Section: Discussionmentioning
confidence: 99%
“…In one study among the older adult population over the age of 75 years, the proportion of severe AS cases found the low-income populations have increased potential need for THA [12][13][14]. Additionally, it may reflect that AS patients were not welcomed by orthopedists or the contribution of AS to mortality and morbidity might have been ignored in the orthopedics department.…”
Section: Discussionmentioning
confidence: 99%